2017
DOI: 10.1038/ncomms15214
|View full text |Cite
|
Sign up to set email alerts
|

Exchange pathways of plastoquinone and plastoquinol in the photosystem II complex

Abstract: Plastoquinone (PLQ) acts as an electron carrier between photosystem II (PSII) and the cytochrome b6f complex. To understand how PLQ enters and leaves PSII, here we show results of coarse grained molecular dynamics simulations of PSII embedded in the thylakoid membrane, covering a total simulation time of more than 0.5 ms. The long time scale allows the observation of many spontaneous entries of PLQ into PSII, and the unbinding of plastoquinol (PLQol) from the complex. In addition to the two known channels, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 45 publications
(69 reference statements)
5
83
0
Order By: Relevance
“…However, more recent data favour a close compartmentization of PSII, PQ-9, and cytochrome b6/f complex in membrane microdomains (Johnson, Vasilev, Olsen, & Hunter, 2014;Lavergne & Joliot, 1991). Moreover, PQ-9 diffusion towards/from PSII was recently proposed to occur via several entries/exits in the PSII reaction centre with an exchange cavity where PQ-9 can diffuse around (Van Eerden, Melo, Frederix, Periole, & Marrink, 2017). These characteristics of the interactions between PSII and PQ-9 are likely to augment the opportunities for reduced PQ-9 to scavenge 1 O 2 produced in the reaction centres.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent data favour a close compartmentization of PSII, PQ-9, and cytochrome b6/f complex in membrane microdomains (Johnson, Vasilev, Olsen, & Hunter, 2014;Lavergne & Joliot, 1991). Moreover, PQ-9 diffusion towards/from PSII was recently proposed to occur via several entries/exits in the PSII reaction centre with an exchange cavity where PQ-9 can diffuse around (Van Eerden, Melo, Frederix, Periole, & Marrink, 2017). These characteristics of the interactions between PSII and PQ-9 are likely to augment the opportunities for reduced PQ-9 to scavenge 1 O 2 produced in the reaction centres.…”
Section: Discussionmentioning
confidence: 99%
“…Inside the exchange channels, PQ was found to be able to reorient (flip-flop), with a flip-flop time much slower (~ 100 μs) than the one observed in bulk membranes (~ 1 μs) (van Eerden et al 2015). PQH2 reorientation was not observed in the cavities, suggesting a much slower flip-flop time for this cofactor (> 200 μs) (Van Eerden et al 2017b). This was attributed to differences in polarity between PQ and PQH2.…”
Section: Beyond the μS Timescale: Interplay Between Pigment-protein Cmentioning
confidence: 92%
“…Via steered MD, the unbinding of quinone and of the reduced anionic semiquinone form was modeled and revealed that the two forms have a similar binding affinity, despite the slower dissociation rate of charged semiquinone (Madeo and Gunner 2005). The stability of quinones at its binding sites was also observed in the case of PQ at a CG resolution (Van Eerden et al 2017b): PQ occupying the Q A and Q B sites from the start of the simulations remained stationary in both sites along the whole trajectories, as expected experimentally (Diner et al 1988;Araga et al 1993;Ermakova-Gerdes and Vermaas 1998). Although no spontaneous binding to the Q B site was observed, PQ was found to enter spontaneously in PSII (Fig.…”
Section: Beyond the μS Timescale: Interplay Between Pigment-protein Cmentioning
confidence: 98%
“…The Martini force field developed by Marrink and coworkers is perhaps the most widely used model for CG simulations of biological membranes. Some examples of recent successes are combination of the force field with the metadynamics method of enhanced sampling to study the energetics of conformational rearrangements in the epidermal growth factor receptor; high throughput simulations showing the effects of alcohol on a mechanosensitive protein; studies of local phase transitions in bacterial membranes induced by an antimicrobial peptide; and unraveling of the plastoquinone exchange pathways of the photosystem II complex . A key advantage of CG models is the ability to self‐assemble the lipid component whether this be a flat bilayer, a micelle, or a small spherical vesicle in the presence or absence of proteins of interest, thereby eliminating the initial “guesswork” of determining how proteins are oriented and packed by the lipids and/or detergents in each environment.…”
Section: Introductionmentioning
confidence: 99%